Photopolarization of Fucus zygotes is determined by time sensitive vectorial addition of environmental cues during axis amplification - Bogaert, Kenny A.; Beeckman, Tom; De Clerck, Olivier (Frontiers in Plant Science, 2015)
Fucoid zygotes have been extensively used to study cell polarization and asymmetrical cell division. Fertilized eggs are responsive to different environmental cues (e.g. light, gravity) for a long period before the polarity is fixed and the cells germinate accordingly. First, it is commonly believed that the direction and sense of the polarization vector are established simultaneously as indicated by the formation of an F-actin patch. Secondly, upon reorientation of the zygote, a new polar gradient is formed and it is assumed that the position of the future rhizoid pole is only influenced by the latter. Here we tested these two hypotheses investigating photopolarization in Fucus zygotes by reorienting zygotes 90° relative to a unilateral light source at different time points during the first cell cycle. We conclude that fixation of direction and sense of the polarization vector is indeed established simultaneously. However, the experiments yielded a distribution of polarization axes that cannot be explained if only the last environmental cue is supposed to determine the polarization axis. We conclude that our observations, together with published findings, can only be explained by assuming imprinting of the different polarization vectors and their integration as a vectorial sum at the moment of axis fixation. This way cells will average different serially perceived cues resulting in a polarization vector representative of the dynamic intertidal environment, instead of betting exclusively on the perceived vector at the moment of axis fixation.